2012
DOI: 10.3109/0284186x.2011.652736
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter results of stereotactic body radiotherapy (SBRT) for non-resectable primary liver tumors

Abstract: (2012) Multicenter results of stereotactic body radiotherapy (SBRT) for non-resectable primary liver tumors, Acta Oncologica, 51:5, 575-583,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 34 publications
2
64
0
2
Order By: Relevance
“…However, if we examine only the IHCC cases, the results of large Surveillance Epidemiology and End Result (SEER) database supports the use of radiation against no treatment (median survival 7 vs. 3 months; p<0.01) [27]. Several other studies have supported the use of radiotherapy in IHCC with median survival ranging from 7-15.3 months with conventional fractionated doses of radiation (45-50 Gy) [28][29][30][31][32]. Furthermore, combination of transarterial chemotherapy with radiation is associated with improved survival (13.3 vs. 7.8 months) [29,30].…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…However, if we examine only the IHCC cases, the results of large Surveillance Epidemiology and End Result (SEER) database supports the use of radiation against no treatment (median survival 7 vs. 3 months; p<0.01) [27]. Several other studies have supported the use of radiotherapy in IHCC with median survival ranging from 7-15.3 months with conventional fractionated doses of radiation (45-50 Gy) [28][29][30][31][32]. Furthermore, combination of transarterial chemotherapy with radiation is associated with improved survival (13.3 vs. 7.8 months) [29,30].…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…Application of SBRT technique in the treatment of HCC with PVTT can make the HCC and PVTT accurately localize high-dose radiation and avoid the surrounding normal liver tissue damage, so as to gain a better therapeutic effect. In the USA, a multicenter clinical trial showed that for the non-resectable HCC patients treated with SBRT, the overall freedom from local progression was 63% at a median follow-up of 12.9 months, the median time to local progression was 6.3 months, the 1-and 2-years overall survival rates were 87% and 55%, respectively [43]. The local and regional recurrence remain the major causes of SBRT failure; further studies of combination of SBRT and other treatment modalities need to be carried out.…”
Section: Radiotherapy (Rt)mentioning
confidence: 99%
“…Certain works limit themselves to the RECIST criteria. [18][19][20][21][22] Other publications apply recommended EASL or mRECIST criteria. [23][24][25][26][27] A single article compared the RECIST and EASL criteria in this indication.…”
Section: Evaluation Of Response After Sbrt For Primary Hepatic Tumorsmentioning
confidence: 99%